2008
DOI: 10.1590/s1415-52732008000400010
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de guias alimentares em diversos países

Abstract: Os guias dietéticos baseados nos alimentos têm objetivo de favorecer a educação nutricional, utilizando termos que sejam compreensíveis, simples e claros para a maioria dos consumidores e indicando as modificações necessárias nos padrões alimentares. Este trabalho foi realizado com o objetivo de apresentar uma revisão da literatura sobre o desenvolvimento dos guias alimentares em vários países. Para tanto, foi realizado um levantamento bibliográfico no período de 1991 a 2006 nas bases de dados Medline e Lilacs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
0
9
0
9
Order By: Relevance
“…However, food guides have not specifically assessed their readers' understanding by FHL. The process of developing food guides is complex, so it is necessary to plan their development and health impact assessment 13 . In this perspective, it is critical to include the variable FHL in the process.…”
Section: Discussionmentioning
confidence: 99%
“…However, food guides have not specifically assessed their readers' understanding by FHL. The process of developing food guides is complex, so it is necessary to plan their development and health impact assessment 13 . In this perspective, it is critical to include the variable FHL in the process.…”
Section: Discussionmentioning
confidence: 99%
“…Steemburgo et al 2 found that 25.4% of the population have chronic diseases and the Metabolic Syndrome (MS). Healthy diets play an important role in the prevention of chronic diseases, and food guides can be a strategy for promoting them 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The agreement between the data collected by the 24hr interviews and the app concerning each variable of interest was assessed using the Pearson's correlation coefficient and the Student's t-test. Additionally, the correlation between the mean values of the portion sizes of food groups consumed (poultry, fish, and eggs; beef and pork; refined grains and breads; fruits and legumes; sugars and sweets, whole grains, tubers and roots; milk and dairy products; animal fats; vegetables and leafy greens; nuts; and vegetable oils) and the Diet Quality Index (GAD) 6 scores obtained by both methods were assessed.…”
Section: E T H O D Smentioning
confidence: 99%
“…On the other hand, excessive intake of refined grains, fats, and added sugars is one of the main factors causing the obesity epidemic 4 . Thus, the knowledge about the population food intake pattern is of great importance 5,6 .…”
Section: Introductionmentioning
confidence: 99%